TI_GERICHTE 15.2013.58 vom 29. Juli 2013 , Pignoramento di salario. Spese dellalloggio. Trasferte e pasti fuori domicilio - TI Tribunale d'appello (2013)
Pignoramento di salario. Spese dell’alloggio. Trasferte e pasti fuori domicilio